Detection of de novo mutations and analysis of their origin in families with X linked hypohidrotic ectodermal dysplasia. Issue 4 (April 1994) - Zonana, J; Jones, M; Clarke, A; Gault, J; Muller, B; Thomas, N S
Abstract : Hypohidrotic ectodermal dysplasia (EDA) has been localised to the q12-q13.1 region of the X chromosome by both physical and genetic mapping methods. Although linkage analysis using closely linked flanking markers can clarify the carrier status for many females at risk for the disorder, knowledge of the origin of the mutation in instances of possible de novo mutation is critical for accurate genetic counselling of families. Two methods have been used to confirm de novo mutation in families with EDA and to trace their origin. Direct detection of three de novo molecular deletions, one arising during oogenesis and the other two during spermatogenesis, was achieved by Southern analyses using cosmids isolated from the EDA region as probes. Seven de novo mutations arising during spermatogenesis, and two possible de novo mutations during oogenesis, were identified by an analysis of the cosegregation of the disorder with polymorphic markers closely linked to and flanking the EDA locus. The confirmation and analysis of the origin of the 10 de novo mutations greatly assisted genetic counselling in these families. The apparent 3.5:1 excess of male to female origin of mutation in families studied with unidentified types of mutation is similar to other studies of X linked disorders, and suggests that the majority of these mutations may involve single base pair substitutions.